2005
DOI: 10.1080/09658210344000567
|View full text |Cite
|
Sign up to set email alerts
|

The earliest memory in individuals raised in either traditional and reformed kibbutz or outside the kibbutz

Abstract: In two studies we compared the age of traditional kibbutz members' first memories with the first memories of people raised in Israeli cities (Study 1) and of people who were raised in reformed kibbutzim (Study 2). Building on the socio-cultural model of autobiographical memory, we predicted and found that children raised in the traditional kibbutz, not by their parents, but by a metapelet, had a significantly later onset of autobiographical memory than children raised in reformed kibbutzim or outside the kibbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Instead, as reviewed above, it is adultÁchild interaction that is more likely to provide for a richer narrative environment (Fivush et al, 2006). Lastly, Harpaz-Rotem and Hirst (2005), in a study comparing individuals raised in traditional kibbutz vs those raised either by their parents only or in a reformed kibbutz setting, found that those from the last two groups reported an earlier average age of first memories due to growing up in environments allowing for more parentÁchild interaction. Even though this work demonstrated that age of memories is related to social factors in the child's environment, the family structure on which they focus is still the nuclear family.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Instead, as reviewed above, it is adultÁchild interaction that is more likely to provide for a richer narrative environment (Fivush et al, 2006). Lastly, Harpaz-Rotem and Hirst (2005), in a study comparing individuals raised in traditional kibbutz vs those raised either by their parents only or in a reformed kibbutz setting, found that those from the last two groups reported an earlier average age of first memories due to growing up in environments allowing for more parentÁchild interaction. Even though this work demonstrated that age of memories is related to social factors in the child's environment, the family structure on which they focus is still the nuclear family.…”
mentioning
confidence: 90%
“…Household composition is an obvious aspect of the sociolinguistic environment that has been taken into account in previous studies of childhood amnesia (Harpaz-Rotem & Hirst, 2005;MacDonald et al, 2000;Mullen, 1994). Researchers found no significant effect of total household size for the age of earliest memory.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Cultural differences emerge in early development, with autobiographical memory and self concept reciprocally influencing each other (Wang, 2006). For example, cultural differences in childrearing practices influence the onset of autobiographical memory, with children raised collectively in reformed kibbutzim reporting later first memories than children raised in more individualistic settings (Harpaz-Rotem and Hirst, 2005). These cultural differences in behavioral measures indicate that the types of social, emotional, and perhaps even sensory processes that contribute to autobiographical memory will differ across cultures based on the contents retrieved from autobiographical memory.…”
Section: Cultural Differences In Sensory and Semantic Systemsmentioning
confidence: 99%
“…Research comparing groups raised with different childrearing practices also supports the idea that the concept of an independent self critically determines the development of autobiographical memory. Children raised collectively in reformed kibbutzim report fi rst memories that occur at a later age than children raised in more individualistic settings (Harpaz-Rotem & Hirst, 2005 ).…”
Section: Cultural Infl Uences On Autobiographical Memorymentioning
confidence: 99%